Step
*
2
of Lemma
qexp-exp
1. n : ℤ
2. 0 < n
3. ∀[x:ℤ]. (x ↑ n - 1 = x^(n - 1) ∈ ℚ)
4. x : ℤ
⊢ x ↑ n = x^n ∈ ℚ
BY
{ xxxxxx(Unfold `exp` 0
         THEN (RWO "primrec-unroll" 0 THENA Auto)
         THEN Reduce 0
         THEN Fold `exp` 0
         THEN (InstHyp [⌜x⌝] 3⋅ THENA Auto))xxxxxx }
1
1. n : ℤ
2. 0 < n
3. ∀[x:ℤ]. (x ↑ n - 1 = x^(n - 1) ∈ ℚ)
4. x : ℤ
5. x ↑ n - 1 = x^(n - 1) ∈ ℚ
⊢ x ↑ n = if (n =z 0) then 1 else x * x^(n - 1) fi  ∈ ℚ
Latex:
Latex:
1.  n  :  \mBbbZ{}
2.  0  <  n
3.  \mforall{}[x:\mBbbZ{}].  (x  \muparrow{}  n  -  1  =  x\^{}(n  -  1))
4.  x  :  \mBbbZ{}
\mvdash{}  x  \muparrow{}  n  =  x\^{}n
By
Latex:
xxxxxx(Unfold  `exp`  0
              THEN  (RWO  "primrec-unroll"  0  THENA  Auto)
              THEN  Reduce  0
              THEN  Fold  `exp`  0
              THEN  (InstHyp  [\mkleeneopen{}x\mkleeneclose{}]  3\mcdot{}  THENA  Auto))xxxxxx
Home
Index